Deep learning strategies for security enhancement in wireless sensor networks - Sagayam, K. Martin 1987-; Bhushan, Bharat; Andrushia, Diana; Albuquerque, Victor Hugo C. de (IGI Global, 2020)
"This book explores the theoretical and practical advancements of security protocols in wireless sensor networks using artificial intelligence-based techniques"--
Description based on title screen (IGI Global, viewed 07/25/2020)
Keywords: Machine learning; Wireless sensor networks / Security measures